IMPLEMENTASI KEPERAWATAN TERAPI RELAKSASI AUTOGENIK PADA IBU HAMIL PRIMIGRAVIDA TRIMESTER III DENGAN ANSIETAS DI DAERAH BINAAN IKEST MUHAMMADIYAH PALEMBANG - Maratun Ulaa (IKesT Muhammadiyah Palembang, 2024)
ABSTRACT Background: Pregnancy is a condition of changes in body image and roles in family members. Pregnant women usually show the same psychological and emotional responses during pregnancy, including ambivalence, acceptance, introversion, mood swings, and changes in body image. To face childbirth, mothers who cannot adapt well will experience anxiety. Anxiety in pregnant women facing childbirth is still quite high. Around 12,230,142 million pregnant women experience problems in the third trimester and 30% (8,561,099) of them have anxiety. If anxiety in pregnant women is not treated seriously, it will have negative impacts and effects on the health of the mother and baby. So it is necessary to provide nursing intervention. One intervention that can be given is autogenic relaxation therapy. Objective: Helping patients to reduce anxiety levels by carrying out autogenic relaxation therapy. Method: This research uses a case study method on two pregnant women with data collection techniques based on the provisions of the inclusion criteria for 6 days from 12 June 2024 to 17 June 2024. Results: After given autogenic relaxation therapy to Mrs.'s anxiety level. M with a score of 26 to 13 and Mrs. T with a score of 26 to 14. Conclusion: The application of autogenic relaxation therapy to primigravida pregnant women in the third trimester has a significant effect on reducing anxiety. Suggestion: Autogenic relaxation therapy can be applied to reduce the level of anxiety in third trimester pregnant women